1982
DOI: 10.1113/jphysiol.1982.sp014193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental salinity on branchial permeability of rainbow trout, Salmo gairdneri.

Abstract: SUMMARY1. The gill fluxes of various non-electrolytes were measured in fresh-water-and sea-water-adapted trout (Salmo gairdneri). The studies were performed in vitro with a 'perfused-head' preparation.2. The results allow one to specify different transepithelial pathways according to the physico-chemical characteristics of the permeant molecules: (1) for hydrophilic and lipophilic molecules of small molecular radius, a transcellular pathway in the respiratory cells of the secondary lamellae, (2) for hexose, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Isaia (1982) demonstrated that gill permeability to small nonelectrolytes, such as urea, was higher in freshwateradapted vs. seawater-adapted rainbow trout. Similar findings were reported by Masoni and Payan (1974) in the eel, Anguilla anguilla.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Isaia (1982) demonstrated that gill permeability to small nonelectrolytes, such as urea, was higher in freshwateradapted vs. seawater-adapted rainbow trout. Similar findings were reported by Masoni and Payan (1974) in the eel, Anguilla anguilla.…”
Section: Discussionmentioning
confidence: 97%
“…Isaia (1982) reported that small nonelectrolytes, such as water and urea, were transported across the gill epithelium by a transcellular pathway. He suggested that these molecules were transported by passive diffusion because there was a linear correlation between their permeability and their oil/water partition coefficients.…”
Section: Urea Transport Mechanismsmentioning
confidence: 99%
“…As one significant difference is expected in 22 tests at the 5% level (statistical type I error), it may be concluded that supplementation of 20 g kg −1 dietary urea during the sea water grow‐out period had little or no effect on the sensory quality of market‐size Atlantic salmon. Isaia (1982) demonstrated that small molecules such as water and urea are almost entirely transported transcellularly through the respiratory cells by passive diffusion. This may explain why a short period of feed deprivation significantly reduced the urea concentration in the muscle to the level of the control group and why no effects on the sensory quality were observed.…”
Section: Discussionmentioning
confidence: 99%
“…A similar muscle urea concentration in trout fed control diet and in those fed diets with and without supplementation, may suggest that excess urea is rapidly excreted. A possible reason for elimination of excess plasma urea may be that small molecules such as water and urea are almost entirely transported transcellularly, by passive diffusion, through the respiratory cells of the secondary lamellae in the gills ( Isaia 1982).…”
Section: Discussionmentioning
confidence: 99%